Molybdenum transmutation via 98Mo samples using bismuth/lead neutron moderators. (7th August 2018) - Khorshidi, Abdollah; Pazirandeh, Ali
Abstract: 99m Tc is the usual medical isotope for imaging in nuclear medicine. The use of accelerators to produce 99 Mo is an alternative to nuclear reactors. Here, the neutron production from a new neutron source is investigated to achieve a proper production yield. The induced neutron was simulated from 30 MeV protons on a beryllium target. The Adiabatic Resonance Crossing (ARC) method was evaluated using lead and bismuth moderators, and lead(II) fluoride reflector around a moderator region. The flux and energy of the aggregated neutrons within different regions of the proposed activator were estimated by the MCNPX code. The epithermal flux in the reflector region was greater than that in the moderator region, since the maximum amount was estimated to be when the bismuth moderator was employed. The outcomes demonstrated that the production yield of 99 Mo improved using the bismuth material, whereas the 98 Mo sample at a distance from the target showed a greater amount by 5.03E + 5 MBq through a 0.1 cm sample thickness. When the sample was positioned in the reflector region, the obtained yield increased taking advantage by the more accumulated flux in the epithermal range. The ARC method can replace conventional reactor-based prototypes of the 99 Mo- 99m Tc generator, or complement them, because it is safe and more accessible.